New concepts in white adipose tissue physiology - Proença, A.R.G. (Associação Brasileira de Divulgação Científica, 2014)
Numerous studies address the physiology of adipose tissue (AT). The interest surrounding the physiology of AT is primarily the result of the epidemic outburst of obesity in various contemporary societies. Briefly, the two primary metabolic activities of white AT include lipogenesis and lipolysis. Throughout the last two decades, a new model of AT physiology has emerged. Although AT was considered to be primarily an abundant energy source, it is currently considered to be a prolific producer of biologically active substances, and, consequently, is now recognized as an endocrine organ. In addition to leptin, other biologically active substances secreted by AT, generally classified as cytokines, include adiponectin, interleukin-6, tumor necrosis factor-alpha, resistin, vaspin, visfatin, and many others now collectively referred to as adipokines. The secretion of such biologically active substances by AT indicates its importance as a metabolic regulator. Cell turnover of AT has also recently been investigated in terms of its biological role in adipogenesis. Consequently, the objective of this review is to provide a comprehensive critical review of the current literature concerning the metabolic (lipolysis, lipogenesis) and endocrine actions of AT.